The Outcomes of Combined Anterior-Posterior Neurectomies as a Primary Approach for Anterior Cutaneous Nerve Entrapment Syndrome - Madi El Haj, MD, MS; Shaul Beyth, MD, PhD; Eliad Davidson; Sofia A. Vorobeitchik; Shilo Kramer, MD; Tal Harel, MD; Rami David, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Anterior cutaneous nerve entrapment syndrome (ACNES) is caused by the entrapment of the terminal branches of intercostal nerves as they pass through the rectus abdominis muscle to innervate the skin. The diagnosis is suggested based on patient history, clinical examination findings, and the absence of objective abnormalities in laboratory or imaging tests. Once suspected, the diagnosis is corroborated by a diagnostic nerve block. When nonoperative treatments fail, anterior neurectomy is the preferred treatment, with a reported success rate of 61%. In refractory cases, combined anterior and posterior neurectomies (AP-neurectomies) serve as the final surgical option. This study aimed to assess the efficacy of primary combined AP-neurectomies in patients unresponsive to conservative treatment. Methods:. A retrospective review was conducted from January 2019 to January 2023, including 26 patients diagnosed with ACNES, who underwent primary combined AP-neurectomies after failed conservative treatment. Preoperative assessments included the 10-point visual analog scale (VAS) for pain, pain rating index, brief pain inventory, and pain catastrophizing scale. Results:. After an average follow-up of 31.63 months postoperatively, 23 (88.5%) patients reported significant pain relief (responders), whereas 3 (11.5%) patients experienced poor outcomes (nonresponders). In the responder group, the preoperative and postoperative VAS scores were 8.26 (range 5–10) and 0.9 (range 0–5), respectively (P < 0.001). There was no correlation between patient age, preoperative pain catastrophizing scale scores, pain duration, and postoperative VAS scores. Conclusions:. Primary combined AP-neurectomies demonstrate an 88.5% success rate in patients diagnosed with ACNES who have persistent symptoms after failed conservative treatments.